The science of intelligent achievement : how smart people focus, create and grow their way to success - Hankel, Isaiah (Capstone, 2018)
"Smart strategies for pragmatic, science-based growth and sustainable achievement. The Science of Intelligent Achievement teaches you the scientific process of finding success through your most valuable assets: Selective focus how selective are you with who and what you let into your life? Creative ownership how dependent are you on others for your happiness and success? Pragmatic growth how consistently and practically are you growing daily? First, this book will show you how to develop your focus by being very selective with where you spend your mental energy. If you've failed to reach an important goal because you were distracted, misinformed, or overcommitted, then you know the role focus and selectivity play in achievement. Second, you will learn how to stop allowing your happiness and success to be dependent on other people and instead, start taking ownership over your life through creative work. Finally, you will learn the art of changing your life through pragmatic decisions and actions. Self-improvement is not the result of dramatic changes. Instead, science has shown that personal and professional change is initiated and sustained by consistent, practical changes. To grow, you must leverage the power of micro-decisions, personality responsibility, and mini-habits. Your own biology will not let you improve your life in any other way. What do you currently value? What are working to attain? Have you been taught to value your job title or your relationship with some other person above all else? Have you been convinced that the most valuable things in life are your paycheck, the number of people who say 'hello' to you at the office, and the number of people who say 'I need you' at home? Or, have you become so passive in what you value that you let anyone and anything into your life, as long as whatever you let in allows you to stay disconnected from the cold hard truth that when things really go wrong in your life, the only person who will be able to fix it and the only person will be responsible for it is you. If sowelcome to fake success. Passivity, dependence, and the sacrifice of practical thinking and personal responsibility to fuzzy, grandiose ideals and temporary feelings these are markers of fake success. Intelligent Achievement, on the other hand, is not a moving target. It's not empty either. Instead, it's sturdy, full, and immovable. It's not something that's just handed to you. It's not something you're nudged to chase or coerced into wanting. Intelligent Achievement comes from within you. It's a collection of values that are aligned with who you are; values you have to protect and nurture. These values do not increase your dependence on other people and things. Instead, they relieve you of dependence. This kind of achievement is something that you have a part in building from the ground upyou know what's in ityou chose it, someone else didn't choose it for you. Achieving real success means you must focus, create, and grow daily. The Science of Intelligent Achievement will show you how"--